Pengaruh Blended Learning Berbantuan Google Classroom Terhadap Hasil Belajar Peserta Didik Kelas X Materi Larutan Elektrolit dan Non Elektrolit di SMA Muhammadiyah 1 Palembang - Rima, Rima Putri Wulan Suci (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
This study aims to determine the effect of the Google Classroom-assisted blended learning model on student learning outcomes on electrolyte and non-electrolyte solutions. The research was conducted at SMA Muhammadiyah 1 Palembang in class X MIPA. The research method uses a quasi-experimental design with a nonequivalent control group design. Students in the experimental class used a blended learning model assisted by google classroom, while students in the control class used a conventional learning model. Based on the results of data analysis, there is a significant difference between the learning outcomes of students in the experimental class and the control class as seen from the Mann Whitney test value, the significance value obtained is 0.000 (p <0.05), it can be concluded that there is a significant effect on the application of the model. blended learning learning assisted by google classroom on student learning outcomes on electrolyte and non-electrolyte solutions.